1994
DOI: 10.1182/blood.v84.2.588.bloodjournal842588
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for nonclonal hematopoietic progenitor cell populations in bone marrow of patients with myelodysplastic syndromes

Abstract: Clonality of marrow hematopoietic progenitor cells in myelodysplastic syndromes (MDS) was analyzed by X-chromosome inactivation pattern using polymerase chain reaction (PCR). Five female patients were included in this study; two with refractory anemia (RA) and three with RA with excess blasts (RAEB). They were heterozygous for BstXI restriction fragment length polymorphisms (RFLP) of the X-chromosome-linked phosphoglycerate kinase (PGK) gene. In each patient, erythroid and nonerythroid colonies, grown in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The rate of administration may play a critical role in erythroid response, and a continuous humoral stimulus on erythroid progenitors in MDS may be necessary to elicit the biological response to rHuEpo, as a post‐translational defect in the Epo response pathway has been demonstrated in MDS, resulting in the suppression of both the Epo‐dependent proliferation and the differentiation induction by Epo (Hoefsloot et al , 1997; Fontenay‐Roupie et al , 1999). The co‐existence of normal haematopoietic progenitors with abnormal ones (Asano et al , 1994) and the presence of certain abnormalities in erythroid progenitors that need higher concentrations of Epo to respond in vitro (Aoki & Shibata, 1992) may suggest that the prolonged administration of rHuEpo enhances stimulation of erythroid progenitors and produces a response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of administration may play a critical role in erythroid response, and a continuous humoral stimulus on erythroid progenitors in MDS may be necessary to elicit the biological response to rHuEpo, as a post‐translational defect in the Epo response pathway has been demonstrated in MDS, resulting in the suppression of both the Epo‐dependent proliferation and the differentiation induction by Epo (Hoefsloot et al , 1997; Fontenay‐Roupie et al , 1999). The co‐existence of normal haematopoietic progenitors with abnormal ones (Asano et al , 1994) and the presence of certain abnormalities in erythroid progenitors that need higher concentrations of Epo to respond in vitro (Aoki & Shibata, 1992) may suggest that the prolonged administration of rHuEpo enhances stimulation of erythroid progenitors and produces a response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that the response to ATG/ALG appears to be related to a ‘non‐clonal’ pattern of bone marrow cells on X‐chromosome inactivation analysis. A detailed review of the pertinent literature revealed a total of 26 ‘polyclonal MDS’ (2, 5–13, 25). Mainly, there are three possible reasons for ‘non‐clonal’ XCIP in patients with MDS.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have also been a few MDS patients with peripheral blood (PB) or bone marrow (BM) cells showing polyclonal X‐chromosome inactivation patterns (XCIP). This observation was attributed to persistence of a considerable amount of normal hematopoiesis (2, 5–13).…”
mentioning
confidence: 99%
“…Myeloid blood cells in MDS, including basophils and eosinophils, may belong to the malignant clone or may represent a mixture of clonal and nonclonal cells [34–36]. Whether the basophils examined in our MDS patients belonged to the malignant clone or not, remains unknown.…”
Section: Discussionmentioning
confidence: 99%